Factors of Ethnic Distance: A Systematic Scoping Review - Šlebir, Miha; Zupančič, Rok (Journal of Ethnic and Cultural Studies, 2024)
Identifying factors determining ethnic distance is a perennial quest in ethnic studies. This is important not only from a theoretical perspective but also as a basis for developing practical interventions aimed at decreasing ethnic distance, which could, in turn, lead to increased tolerance and social peace. Building on existing research, we conducted a systematic scoping review of 30 studies to identify prevalent factors and variables that significantly impact individuals’ ethnic distance. According to our study, the most relevant variables are gender, education, income, age, interethnic contact, war experience, following news in the media, religious commitment, religious denomination, and political orientation. The analysis has shown that these variables can be grouped into four distinct factors: sociodemography, exposure, religion, and politics. However, none of the factors and variables identified were found to be universally applicable, as the cause of ethnic distance is multifactorial and context-dependent. We mapped the characteristics of existing studies, focusing on any indication of psychological mechanisms driving the changes in interethnic (in)tolerance. Most of the studies reviewed were based on the Bogardus scale, a commonly used tool for measuring ethnic distance.